A Critique on the Book “Catalogue of Manuscripts on Alchemy and Related Sciences within Iranian Libraries” - Ali Kavousi-rahim (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of the present paper is to criticize the “Catalogue of Manuscripts on Alchemy and Related Sciences within Iranian Libraries” by Zohre Māziār and Nasibe Ranjbardār, which has been published in 2013/1392, along with an introduction made by Yousof Beyg Bābāapour.  Nowadays, since the research on Islamic alchemy is in its infancy, the compilation of such a catalog could be acknowledged as a necessary reference for future studies on alchemy. The importance of a catalog comes from this way that it is the connective ring between ancient manuscripts and their editors. But, as concluded in this paper, that contribution would not be useful in the subject, in spite of its proper title. In the present critical analysis, we have remarked six major deficiencies of this catalog. Exclusive quotation from previously published DENA catalog without appropriate referencing to it, frequent writing mistakes and omitting a significant number of manuscripts could be reported as three major defects of this catalog. In my opinion, this catalog shall mislead the researchers in their way to detect the manuscripts instead of guiding them in a right path.